Tourism in inland areas. A Talk with Claudio Milano - Freire Varela, Antón (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Antón Freire Varela Tourism in inland areas. A Talk with Claudio Milano